Depression Among Elderly Women in Rural Mandya, Karnataka: A Cross Sectional Study - Sivapria KA; Manuja LM; Vinay M; Raghavendra Kumar C; Harish BR (National Journal of Community Medicine, 2023)
Background: Depression is characterized by persistent sadness and lack of interest or pleasure in enjoyable activities and disturbed sleep and appetite. Women suffer from depression the most, as the hurdles faced by Indian women include lack of awareness, stigma, disadvantaged position of women, multiple roles, increased levels of stress, and domestic violence. This study is to determine the prevalence of depression among elderly women and to determine the factors affecting it. Methodology: This cross-sectional study was conducted among 783 elderly women (aged 60 years or more), residing in rural Mandya (South Karnataka) by interviewing them using a semi-structured proforma. Geriatric Depression Scale (GDS-15) was used to assess depression. Mean, standard deviation and proportion were used for descriptive statistics. Chi square test was used to determine association of risk factors. Results: The prevalence of depression was found to be 31.6%. The major factors affecting depression were increasing age, illness and loneliness. Conclusions: The prevalence of depression in the elderly women was high (31.6%). By identifying risk factors for depression among the elderly population and screening them on time, we can reduce the severity and burden of the disease to a greater extent.